Influence of antiretroviral therapy and cardiovascular disease on the immature platelet fraction in patients living with HIV. (17th August 2020) - Goedel, A.; Müller, S.; Schwerdtfeger, C.; Zink, A.; Noe, S.; Bongiovanni, D.; Haller, B.; Spinner, C. D.; Bernlochner, I.
Abstract: Cardiovascular disease is an important contributor to morbidity and mortality in people living with HIV . The immature platelet fraction (IPF) is increased in HIV-negative patients with cardiovascular disease and evidence suggests that an enlarged IPF is associated with adverse cardiovascular events. In this multi-center observational study, we aimed to investigate how the IPF in people living with HIV is influenced by antiretroviral therapy and cardiovascular disease. Subjects without cardiovascular disease that received antiretroviral therapy showed a smaller IPF accompanied by lower D-dimer and C-reactive protein (CRP) levels compared to therapy-naïve subjects (mean IPF: 2.9% vs. 3.9%, p = .016; median D-dimer: 252 µg/L vs. 623 µg/L, p < .001; median CRP: 0.2 mg/dL vs. 0.5 mg/dL, p = .004). No significant differences for the IPF, D-dimer or CRP were found between subjects on antiretroviral therapy with documented cardiovascular disease and therapy-naïve subjects. In conclusion, we observed a reduction in the IPF among subjects on therapy only in the absence of cardiovascular disease. In contrast, subjects receiving therapy that had documented cardiovascular disease showed an IPF comparable to therapy-naïve subjects. Future studies are needed to investigate if an enlarged IPF may serve as a biomarker in predicting adverse cardiovascular events in people living with HIV.